Tobacco Treatment Outcomes for Hospital Patients With and Without Mental Health Diagnoses - Sanford, Brandon T.; Toll, Benjamin A.; Palmer, Amanda M.; Foster, Madeline G.; Cummings, K. Michael; Stansell, Stephanie; Rojewski, Alana M. (Frontiers in Psychiatry, 2022)
Background: The prevalence of mental health problems is higher in cigarette smokers than nonsmokers. However, those with diagnosed mental health disorders are understudied within general inpatient hospital settings. This study seeks to evaluate how having a mental health diagnosis influences response to a brief opt-out inpatient tobacco treatment intervention. Methods: Data included 4,153 admitted patients who completed a tobacco treatment visit. Post-discharge self-reported abstinence was obtained via response to an automated call 1-month after discharge. Mental health co-morbidities were assessed by reviewing electronic medical records. Logistic regression was used to assess associations between having a mental health diagnosis and patients’ smoking history, interest in quitting smoking, and post-discharge abstinence. Results: Overall 34.1% of patients were positive for having a diagnosed mental health disorder. Patients with a diagnosed mental health disorder were more likely to report a history of long-term heavy smoking and were less likely to express an interesting in remaining abstinent from smoking after hospitalization. An intent-to-treat analysis using logistic regression analysis found lower rates of self-reported smoking abstinence in those with a mental health disorder compared to those without (9% vs 13.2%, p<0.001) Conclusions: Having a history of mental health problems was associated with lower rates of smoking abstinence in patients after hospitalization. Hospital based opt-out smoking cessation programs have shown to be generally effective and efficient. However, certain subpopulations may require tailored intervention in order to improve treatment outcomes. Future research is needed to develop brief, effective tobacco treatment for hospital patients with comorbid mental health diagnoses.